PENGARUH PERSEPSI, MOTIVASI, PENGETAHUAN AKUNTANSI, JANGKA WAKTU STUDI TERHADAP MINAT MELANJUTKAN STUDI PADA PROGRAM PENDIDIKAN PROFESI AKUNTANSI - Budiarso, Novi S.; Wullur, Magdalena; Dotulong, Lucky O. H. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
The program for accounting study in Indonesia had many changes since 1960, and the most significant is in the 2001 when National Education Ministry issued decree No. 179/U/2001 about Accountancy Profession Program. This program is intended for bachelor who want get their Accountant degree, because before 2004 every bachelor had their Accountant degree automatically. This study finds that perception, knowledge of accounting, and time for study are significantly affect the interest for bachelor to continue their study at Accountancy Profession Program.